Competitive release and outbreaks of non‐target pests associated with transgenic Bt cotton. Issue 4 (June 2016) - Zeilinger, Adam R.; Olson, Dawn M.; Andow, David A.
Abstract: The adoption of transgenic Bt cotton has, in some cases, led to environmental and economic benefits through reduced insecticide use. However, the distribution of these benefits and associated risks among cotton growers and cotton‐growing regions has been uneven due in part to outbreaks of non‐target or secondary pests, thereby requiring the continued use of synthetic insecticides. In the southeastern USA, Bt cotton adoption has resulted in increased abundance of and damage from stink bug pests, Euschistus servus and Nezara viridula (Heteroptera: Pentatomidae). While the impact of increased stink bug abundance has been well‐documented, the causes have remained unclear. We hypothesize that release from competition with Bt‐ susceptible target pests may drive stink bug outbreaks in Bt cotton. We first examined the evidence for competitive release of stink bugs through meta‐analysis of previous studies. We then experimentally tested if herbivory by Bt ‐susceptible Helicoverpa zea increases stink bug leaving rates and deters oviposition on non‐ Bt cotton. Consistent with previous studies, we found differences in leaving rates only for E. servus, but we found that both species strongly avoided ovipositing on H. zea‐ damaged plants. Considering all available evidence, competitive release of stink bug populations in Bt cotton likely contributes to outbreaks, though the relative importance of competitive release remains an open question. Ecological risk assessments of Bt crops and other transgenic insecticidal crops would benefit from greater understanding of the ecological mechanisms underlying non‐target pest outbreaks and greater attention to indirect ecological effects more broadly.